PALAEOMAGNETIC AND ROCK-MAGNETIC STUDIES OF CRETACEOUS ROCKS IN THE GONGJU BASIN, KOREA: IMPLICATION OF CLOCKWISE ROTATION - Doh S.Ja.; Kim W.; Suk D.; Park Y.H.; Cheong D. (My University, 2002)
Palaeomagnetic and rock-magnetic studies have been carried out for Cretaceous non-marine sedimentary rocks (Gongju Group) and volcanic rocks in the Gongju Basin, located along the northern boundary of the Ogcheon Belt, Korea. K-Ar age dating for the volcanic rocks was also performed. It is found that the Gongju Group was remagnetised during the tilting of the strata with the characteristic remanent magnetisation (ChRM) direction of &formmu0; at 30 per cent untilting of the strata with a maximum value of precision parameter (k ), while the volcanic rocks are revealed to acquire primary remanence with the direction of &formmu1; after the tilt-correction. The K-Ar ages of the volcanic rocks range from $81.8 ± 2.4$ to $73.5 ± 2.2 Ma$, corresponding to the Campanian stage of the Late Cretaceous. Electron microscope observations of samples from the Gongju Group show authigenic iron-oxide minerals of various sizes distributed along the cleavage of chlorite and in the pore spaces, indicating that the strata acquired the chemical remanent magnetisation due to the formation of secondary magnetic minerals under the influence of fluids. The palaeomagnetic pole positions are at Lat./Long. = 69.6°N/224.3°E $(dp = 3.5°, dm = 5.2°)$ calculated for the 30 per cent tilt-corrected direction of the Gongju Group and at &formmu5; for the volcanic rocks. Based on the results of this study, it is interpreted that the volcanic rocks acquired the primary magnetisation almost at the same time as the remagnetisation of the Gongju Group in the Late Cretaceous. Comparisons of Cretaceous palaeomagnetic poles from the Korean Peninsula with those from Eurasia implies that the Korean Peninsula underwent clockwise rotation of $21.2°± 5.3°$ for the middle Early Cretaceous, $12.6°± 5.4°$ for the late Early Cretaceous, and $7.1°± 9.8°$ for the Late Cretaceous with respect to Eurasia, due to the sinistral motion of the Tan-Lu Fault.
Keywords: CRETACEOUS; GONGJU BASIN; KOREA; PALAEOMAGNETISM; REMAGNETISATION; ROTATION; Mesozoic::Cretaceous; Мезозой::Меловая